Komposisi Proksimat pada Tiga Varietas Tepung Labu Kuning (Cucurbita Sp) - Mardiah, Mardiah; Fitrilia, Tiana; Widowati, Sri; Andini, Sumi Fitri (JURNAL AGROINDUSTRI HALAL, 2020)
Pumpkin is a horticultural product that contains many components of nutrients. Making pumpkin flour is expected to extend the shelf life and can be widely used in food product applications. This study aims to make flour from three varieties of pumpkin (Pumpkin, Kabocha and Butternut) and than knowing the proximate composition of each pumpkin flour. The methode used in making flour was started with soaking pumpkin in sodium metabisulfite and drying using Tray Dryer. The results showed that the proximate composition of Pumpkin, Kabocha and Butternut sequentiall had water content value 14.18%; 11.02% and 13.28%, ash content 8.05%; 10.0% and 8.88%, fat content 4.51%; 1.58% and 1.55%, protein content 11.56%; 14.74% and 7.32%, carbohydrate 61.71%; 62.62% and 68.97% and energy value 333.64 kal; 323.61 kal and 319.12 kal. Keywords: Pumpkin, pumpkin flour, proximate